Who did what; the lives and achievements of the 5000 men and women--leaders of nations, saints and sinners, artists and scientists--who shaped our world (New York : Crown Publishers, 1974)
Brief alphabetically arranged biographical sketches of 5000 men and women representing a variety of professions and nationalities.
Keywords: Biography -- Dictionaries; Biography